Young people's policy recommendations on algorithm fairness - Perez, Elvira; Koene, Ansgar; Portillo, Virginia; Dowthwaite, Liz; Cano, Monica (2017)
This paper explores the policy recommendations made by young people regarding algorithm fairness. It describes a piece of ongoing research developed to bring children and young people to the front line of the debate regarding children's digital rights. We employed the Youth Juries methodology which was designed to facilitate learning through discussions. The juries capture the deliberation process on a specific digital right, the right to know how algorithms govern and influence the Web and its users. Preliminary results show that young people demand to know more about algorithms, they want more transparency, more options, and more control about the way algorithms use their personal data.